Complete sequence and transcriptional analysis of the spo0F region of the Bacillus subtilis chromosome. - Trach, K (1988)
The total sequence of a 6,314-base-pair BglII fragment of the Bacillus subtilis chromosome containing the spo0F locus has been accomplished. Several genes of interest have been identified on this DNA fragment. The ctrA locus was recognized as coding for CTP synthetase by comparison of its deduced sequence with that of Escherichia coli CTP synthetase. A total of 53% of the residues are identical between the enzymes from these organisms. The spo0F locus was followed immediately by a locus, tsr, required for RNA synthesis in this organism. Temperature-sensitive mutations within the tsr locus have been identified, but strains with deletions of the locus are nonviable. It was concluded that tsr codes for an unknown essential component of the RNA synthesis machinery. The tsr gene was followed by another open reading frame which could code for a protein of 19,975 Mr. This gene was translated in vivo, but deletion-insertion mutations within the gene had no phenotype. The gene was cotranscribed with the tsr gene, although about 50% of the transcripts terminated between the two genes. The rev-4 mutation which reverts the sporulation-defective phenotype of erythromycin-resistant mutants was located to a partial open reading frame at the end of the fragment. Disruption of this open reading frame by deletion-insertion mutation did not result in a discernible phenotype. S1 protection experiments located the start sites of transcription for several of the genes on this fragment. The spo0F gene was found to be monocistronic. Regulation of the identified genes was investigated by using beta-galactosidase gene fusions.